Recent Developments in the Synthesis of 1,2,5-Thiadiazoles and 2,1,3-Benzothiadiazoles - Rakitin, Oleg A. (Synthesis, 2019)
The fast-growing interest in 1,2,5-thiadiazoles and their fused analogues including 2,1,3-benzothiadiazoles in recent years as important compounds in materials science and biomedicine has led to great progress in the synthesis of these heterocyclic systems. In this short review, the development of known procedures together with novel reactions is covered. New starting materials, unknown and unexpected transformations for the construction of the thiadiazole ring are emphasized.1 Introduction2 Synthesis of Monocyclic 1,2,5-Thiadiazoles2.1 From 1,2-Diamines, vic-Dioximes and Related Compounds2.2 From Alkyl Aryl (Hetaryl) Ketoximes and Tetrasulfur Tetranitride2.3 By Condensation Reactions2.4 From Other Heterocycles3 Synthesis of Fused 1,2,5-Thiadiazoles3.1 From ortho-Phenylenediamines and Related Compounds3.2 From ortho-Aminonitroso and ortho-Aminonitro Derivatives3.3 By Condensation Reactions3.4 By Chalcogen Exchange in 1,2,5-Oxa- and 1,2,5-Selenadiazoles3.5 Miscellaneous Methods4 Conclusions
Keywords: 1,2,5-thiadiazole; 2,1,3-benzothiadiazole; chalcogen exchange; disulfur dichloride; condensation